Book Review âSustainable Poem Parkâ (Malay Version) - Pinang, Pulau (Social Science Learning Education Journal, 2017)
Edited by Md Salleh Yaapar, poetry is an art form spoken Malay that can also be expressed in writing. As a literary genre, it has long been used by various communities in the Malay Archipelago. Its fans include nomadic and Western researchers were amazed by the delicacy and beauty of the message form. The first poem (which is somewhat less than perfect) brought to the West is the following: Souda malam siappa de pintoeu, Anak Banda tester casomba;Â  Mari masssoek jangan takot,Â  Lakii beta adda cotta. This poem is contained in a book in Latin about the Malay language grammar published in 1688.